Pengaruh Video Tutorial Gerak Dasar Lokomotor Berbasis Canva Terhadap Kemampuan Melompat Jauh Siswa Kelas IV di UPTD SD Negeri Telang 2 Kamal - Rina Angelia; Kusmiyati Kusmiyati (Yayasan Citra Dharma Cindekia, 2025)
This study aims to analyze the effect of a Canva-based basic locomotor movement tutorial video on the long jump ability of fourth-grade students at UPTD SD Negeri Telang 2, Kamal District. The research method used is an experimental design with pre-test and post-test. The subjects of the study consisted of 30 students, divided into two groups: an experimental group using the tutorial video and a control group using conventional teaching methods. A pre-test was conducted to measure the students' initial abilities, while the post-test was conducted after six sessions of intervention. The results show that the experimental group experienced a significant improvement in their long jump ability, with the average jump distance increasing from 1.5 meters (pre-test) to 2.3 meters (post-test). In contrast, the control group only showed an improvement from 1.4 meters to 1.7 meters. Data analysis using the t-test produced a p-value of 0.001, indicating a significant difference between the two groups. These findings suggest that the use of a Canva-based tutorial video is effective in improving students' long jump abilities and can be an innovative alternative teaching method in physical education.